ROCK SLOPE STABILITY PROBLEMS IN NATURAL SIGHTSEEING AREAS - AN EXAMPLE FROM ARVANITIA, NAFPLIO, GREECE - Loupasakis, C.; Galanakis, D.; Rozos, D. (Bulletin of the Geological Society of Greece, 2010)
The morphological and geological setting of Greece, the active tectonics and the irrational human activities results to the fact that several natural sightseeing areas or even more, archaeological sites and monuments are located in areas with unfavourable geotechnical conditions. The selection of the proper support and protection measures in most of the cases appear to be very difficult because the applied measures must reassure the minimum aesthetic destruction of the sites. The natural sightseeing area of the Arvanitia walkway, in Nafplio city, is a typical example of site, with extensive human activities, manifesting serious rockfall stability problems. The applied stability analysis pointed out the geotechnical problems and allowed the suggestion of measures for the improvement of the geotechnical behaviour of the rock mass. The measures were planned with respect to the natural beauty and the historical character of the site. Further more, the stability problems located at the slopes of the Kastoria lake walkway are briefly presented. The differences between the two sites revealed the geotechnical problems arising when the landplaning engineers do not take under consideration the engineering geological conditions during the construction of infrastructures.